Evolution of a mushy zone in a static temperature gradient using a volume average approach - Phillion, A.B.; Založnik, M.; Spindler, I.; Pinter, N.; Aledo, C.-A.; Salloum-Abou-Jaoude, G.; Nguyen Thi, H.; Reinhart, G.; Boussinot, G.; Apel, M.; Combeau, H. (My University, 2017)
A volume average model to study the transition of a semi-solid mushy zone to a planar solid/liquid interface in a static temperature gradient is presented. This model simulates the principal phenomena governing mushy zone dynamics including solute diffusion in the interdendritic and bulk liquids, migration of both the solid-liquid interface and the mushy-liquid boundary at the bottom and top of the mushy zone, and solidification. The motion of the solid-liquid interface is determined analytically by performing a microscopic solute balance between the solid and mushy zones. The motion of the mushy-liquid boundary is more complex as it consists of a transition between the mushy and bulk liquid zones with rapidly changing macroscopic properties. In order to simulate this motion, a control volume characterized by continuity in the solute concentration and a jump in both the liquid fraction and the solute concentration gradient was developed. The volume average model has been validated by comparison against prior in-situ X-ray radiography measurements [1], and phase-field simulations [2] of the mushy-to-planar transition in an Al-Cu alloy. A very good similarity was achieved between the observed experimental and phase-field dynamics with this new model even though the described system was only one-dimensional. However, an augmentation of the solute diffusion coefficient in the bulk liquid was required in order to mimic the convective solute transport occurring in the in situ X-ray study. This new model will be useful for simulating a wide range of natural and engineering processes.
Keywords: Solidification; Volume averaging method; Phase field method; Synchrotron X-ray radiography; Temperature gradient zone melting